2020
DOI: 10.1177/1934578x20931965
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Potential Antibreast Cancer Components From Prunellae Spica Using MCF-7 Cell Extraction Coupled with HPLC-ESI-MS/MS

Abstract: Prunellae Spica (PS), the dry spikes of Prunella vulgaris L., is a medicinal herb widely distributed in Asia and Europe. As a traditional Chinese medicine, PS has been used for the treatment of mastitis, infectious hepatitis, and hypertension. The oral solution and some compounds (polysaccharide, ursolic acid, and betulinic acid) of PS have been reported to show activities against breast cancer. In this study, Michigan Cancer Foundation-7 (MCF-7) cell extraction coupled with high-performance liquid chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Another team of Chinese researchers quantified 4 phenol-carboxylic acids using an HPLC-ESI-MS/MS method for the screening of potential antineoplastic compounds in breast cancer (Yang A et al): protocatechuic, caffeic, rosmarinic acids and protocatechualdehyde. The study did not analyse the other polyphenols (flavonoids) present [54]. Previously, Ba Y and Wang Y (2017), using an HPLC-UV method with DAD detector, quantified caffeic and chlorogenic acids in Prunella vulgaris L. in order to study their antiproliferative effect on cancer cells of the thyroid (K1) [6].…”
Section: Representative Images Of Ulcers and Associated Lesions In Thmentioning
confidence: 99%
“…Another team of Chinese researchers quantified 4 phenol-carboxylic acids using an HPLC-ESI-MS/MS method for the screening of potential antineoplastic compounds in breast cancer (Yang A et al): protocatechuic, caffeic, rosmarinic acids and protocatechualdehyde. The study did not analyse the other polyphenols (flavonoids) present [54]. Previously, Ba Y and Wang Y (2017), using an HPLC-UV method with DAD detector, quantified caffeic and chlorogenic acids in Prunella vulgaris L. in order to study their antiproliferative effect on cancer cells of the thyroid (K1) [6].…”
Section: Representative Images Of Ulcers and Associated Lesions In Thmentioning
confidence: 99%
“…In this regard, new data on chemical constituents from different parts of PV extracts using various solvents, which were not covered earlier in other reviews, have been added to Table 2 . The data obtained by the authors of [ 52 , 53 ] showed that rosmarinic acid was the main component of aqueous extracts of PV. To confirm this fact, [ 52 ] we additionally carried out the HPLC analysis using a standard sample of rosmarinic acid.…”
Section: Chemical Composition Of Pv Plant Partsmentioning
confidence: 99%
“…Oleanolic acid from PVL, was proved to induce apoptosis of lung adenocarcinoma cells by down-regulating the expression of Bcl-2 and up-regulating the expression of Bax and Bad ( Feng et al, 2011b ). In addition, Yang et al proved through experiments that the protocatechuic aldehyde and caffeic acid derived from PVL exhibited obvious cytotoxicity to Michigan Cancer Foundation-7 (MCF-7) cell ( Yang et al, 2020 ).…”
Section: Pharmacologymentioning
confidence: 99%